Shipper's perceptions of aviation Logistics Service Quality (LSQ) of air freight provider - Rahman, N.A.A. (Medwell Journals, 2018)
This research investigates logistics service quality of the air freight provider from a shipper's perspective in Malaysia. The multiple empirical case studies are used to collect data from the shipper':s perspective. Findings suggest there are five main factors that represent air freight service quality of the air freight provider. They are ground handler attitude, fast delivery, communication and information sharing, product reliability and price. These findings contribute to the current theory of Logistics Service Quality (LSQ) with specifically enhance our understanding of air freight service quality. These findings contribute to the current theory of air freight service quality where it is still underdeveloped. This research studies LSQ from shippers perspective only. Findings from this study has developed better our current understanding of logistics service, particularly in air freight sector. Thus, this study is pioneer that offers a study on LSQ in air freight perspective and explore the elements of air freight service quality. Findings from this study not only enhance current knowledge on air freight LSQ but also assist the government to help air freight provider to support themselves as a preparation to become the major player of Aeropolis city in Malaysia. Â© Medwell Journals, 2018.